ANALISIS PERAN TEKNOLOGI INFORMASI DALAM MENINGKATKAN EFISIENSI PEMASARAN - Dyah Ayu wulandari; Munifah Munifah; Haris Ihsanil Huda; Agustinus Wardi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
The rapid development of information technology (IT) in the digital age has brought significant changes to various aspects of life, including the business world. IT not only makes it easier for people to carry out their daily activities, but also contributes greatly to data management and the delivery of relevant, fast, and accurate information. One of the tangible impacts of IT development can be seen in the field of marketing. The transition from traditional marketing to digital marketing enables companies to reach a broader market with moreefficient costs and more targeted strategies. Social media and digital platforms such as e-commerce have become effective tools for expanding product distribution, enhancing communication with consumers, and streamlining businessoperations. Digitalization also presents opportunities for innovation and economic growth through the use of electronic payment systems and internet-based business management. Therefore, the integration of information technology into marketing strategies is a crucial factor in creating competitiveadvantages and operational efficiency in the modern era. Keywords: Information Technology, Digital Marketing, E-commerce, Business Efficiency, Digitalization.